(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The present study was conducted to evaluate the adaptability and characterize Boer goat morphometrically under the farming condition of Bangladesh. Data on adaptability and characterization were collected from the imported flock of Boer goat maintained at American Dairy Limited, Sreepur, Gazipur. A total of 31 Boer goats (15 males and 16 females) at birth (0), 3, 6, 9, and 12 months of age were considered for morphometric characterization. From the study, it was revealed that Boer goats were adapted easily in our climatic and farming conditions. All the body measurements (body length, heart girth, height at wither, head length, head width, ear length, ear width, tail length) in both sexes were significantly (p<0.05) varied at birth (0), 3, 6, 9 and 12 months of age. The body length at the age group of 0, 3, 6, 9 and 12 months were 23.19±1.13 vs 21.44±0.78 cm, 45.36±1.21 vs 44.88±0.79 cm, 63.23±1.09 vs 59.57±1.13 cm, 72.13±1.12 vs 64.66±1.18 cm, and 86.33±1.42 vs 75.83±1.43 cm, for male vs female Boer goats, respectively. Adult male Boer goats had significantly higher (p<0.05) body length, heart girth, height at wither, ear length, ear width than adult female goats but sex did not influence (p>0.05) the head length, head width and tail length. Scrotal circumference significantly (p<0.001) differed in different age groups and corresponding values were 8.02±0.44, 11.91±0.54, 21.78±0.42, 24.43±0.41 and 26.22±0.40 cm at 0, 3, 6, 9 and 12- month of age, respectively. On the other hand, birth weight of male goats (2.90±0.09 kg) were higher (p>0.05) than female (2.29±0.09 kg) goats. However, body weights differed significantly (p<0.001) between male and female at the later ages where male attainted 32.56±0.69 kg, 45.56±1.19 kg and female attained 24.33±0.97 kg, 32.78±1.29 kg at 6- and 12 month of ages, respectively. These results suggested that Boer goats are adaptable in the farming condition of Bangladesh as well as attained standard birth weight and higher adult body weight that can be used to mitigate the huge demand of meat in Bangladesh. J Bangladesh Agril Univ 18(2): 428–434, 2020 https://doi.org/10.5455/JBAU.98621